2021
DOI: 10.1021/acs.energyfuels.0c04148
|View full text |Cite
|
Sign up to set email alerts
|

Study of Emissions from Domestic Solid-Fuel Stove Combustion in Ireland

Abstract: Solid-fuel stoves are at the heart of many homes not only in developing nations, but also in developed regions where there is significant deployment of such heating appliances. They are often operated inefficiently and in association with high emission fuels like wood. This leads to disproportionate air pollution contributions. Despite the proliferation of these appliances, an understanding of particulate matter (PM) emissions from these sources remains relatively low. Emissions from five solid fuels are quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Domestic solid fuel burning can be a great health concern as studies have shown that solid fuel burning OA can be more toxic than other sources [ 9 , 15 ], although the toxicities of peat burning, the dominant solid fuel burning OA factor found in this region, remain poorly investigated in comparison with other solid fuels of wood and coal combustion. Considering that solid fuel burning emissions are directly linked to local heating activities, in theory, it can be reduced through the replacement of dirty fuels by cleaner fuels (e.g., gas or electricity) or using a more efficient wood stove instead of an open stove with no emission control [ 46 ]. However, in practice, emission control of solid fuel burning is challenging given that solid fuel is one of the major and cheap heating sources available for some households [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Domestic solid fuel burning can be a great health concern as studies have shown that solid fuel burning OA can be more toxic than other sources [ 9 , 15 ], although the toxicities of peat burning, the dominant solid fuel burning OA factor found in this region, remain poorly investigated in comparison with other solid fuels of wood and coal combustion. Considering that solid fuel burning emissions are directly linked to local heating activities, in theory, it can be reduced through the replacement of dirty fuels by cleaner fuels (e.g., gas or electricity) or using a more efficient wood stove instead of an open stove with no emission control [ 46 ]. However, in practice, emission control of solid fuel burning is challenging given that solid fuel is one of the major and cheap heating sources available for some households [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…During torrefaction, the biomass is heated to 225–275 °C, driving off water and semivolatiles which can be used as a fuel to drive the process. Torrefaction also contributes to structural changes in the fuel through breaking hemicellulose, lignin, and cellulose chains at elevated temperatures . The result is a high energy density fuel with up to 50% mass loss, but with little total energy loss.…”
Section: Emissions Factors and Mitigation Strategies For Biomass Comb...mentioning
confidence: 99%
“…PM was dominated by fine particles (200–320 nm) and emissions factors varied in the range 38–350 g/GJ. Trubetskaya et al recently studied PM emissions factors from the combustion of a range of fuel types in both a conventional and an EDD compliant wood stove . They found that the use of secondary air could reduce PM from wood logs by about two-thirds due to improved mixing of fresh air with preliminary combustion products.…”
Section: Emissions Factors and Mitigation Strategies For Biomass Comb...mentioning
confidence: 99%
“…Elsasser et al found that the organic matter was the main contributor to the total mass of particles during the measurements performed by means of an Aerodyne aerosol mass spectrometer (AMS) in a different burning phase of a 30 kW log wood boiler (approximately 93%). Likewise, a more recent study, which compared two PM measurement methods (“Hot filter” and AE33 aethalometer coupled with an Aerosol Chemical Speciation Monitor) through combustion tests using a “conventional” and an Ecodesign stove using five different solid fuels, also found that organic matter dominated PM composition in the range between 50 and 95% . So, reducing the contribution of domestic biomass combustion to ambient air particulate matter concentrations does imply reducing not only solid particulate matter emissions but also those of the condensable fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Portable methods based on dilution of part flow sampling such as CTM-039 can be used to collect both solid and condensable fractions of PM from combustion processes. The influence of PM measurement methods used on the reported EF has previously been documented by Nussbaumer et al, Seljeskog et al, and most recently by Trubetskaya et al Nussbaumer et al proposed a detailed survey and review of the various emission factors used in Europe, also in relation to the type of measurement techniques. They showed how emission factors varied between measurements of solid particles (indicated as SP), solid particles plus condensables found collected thanks to an impinger (SPC), and total particles collected in a dilution tunnel.…”
Section: Introductionmentioning
confidence: 99%